The Method of Surgical Lip Repair Affects Speech Outcomes in Children With Bilateral Cleft Lip and Palate. (April 2021) - Peryer, Holly; Slator, Rona; Thomson, Jenny; Richard, Bruce
Objective: It was hypothesized that lip repair protocols in children with bilateral cleft lip and palate (BCLP) would affect development of bilabial consonants /m/ /b/ /p/. This study compared speech outcomes in 2 surgical groups. Design: A retrospective case note investigation. Setting: UK Cleft Centre (2000-2009). Patients: Forty-nine children with complete BCLP, of whom 26 had a 1-stage and 23 a 2-stage bilateral cleft lip repair. Interventions: One-stage cleft lip repair versus a 2-staged cleft lip repair. Main Outcome Measures: Bilabial consonant production at 18 months, 3 and 5 years of age. Cleft Speech Characteristics (CSCs) at age 5. Results: At age 18 months, 81% of the 1-stage lip repair group and 4% of the 2-stage lip repair group produced bilabial consonants ( P <·0001, Fisher test). At age 3 years, 81% of the 1-stage and 26% of the 2-stage lip repair groups produced bilabial consonants ( P =·0133, Fisher test). At age 5 years, both groups had similar bilabial consonant production, but children in the 2-stage lip repair group had more frequent and severe CSCs ( P = ·0037, χ 2 ). Conclusion: A 1-stage lip repair for children with complete BCLP resulted in better bilabial consonant production at 18 months and 3 years of age than a 2-stage lip repair. At age 5 years both groups had bilabial consonants but children in the 2-stage lip repair group had worse CSCs. The surgical protocol for bilateral cleft lip repair affected speech outcome in children with BCLP.